Аналіз та моделювання макроекономічних процесів у перехідний період - Gogoladze, N. G. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The paper is devoted to construction of mathematical models for inflation and transforming the property form or privatization. The models constructed are used for the optimal control problem statement aiming to compute optimal trajectories for the processes implementation. To solve the optimal control problem dynamic programming method is applied. As a result of the problem solving analytical expressions were derived for optimal inputs, and respective optimal trajectories were computed for various initial conditions.